Penerapan Konsep Community Based Tourism (CBT) dalam Pengembangan Kawasan Wisata di Kabupaten Pohuwato - Rahmat Landjani; Nevi Kurniawati; Liberty Lodjo (TOBA: Journal of Tourism, Hospitality, and Destination, 2024)
The concept of Community Based Tourism (CBT) is one of the concepts in the development of tourist areas that involve local communities in developing and managing tourism activities in an area. Objectives: of this research are: 1) to determine the form of application of the Community Based Tourism concept in the development of the Tourism Area of Pohon Cinta Beach and Lahe Island; 2) to identify the supporting and inhibiting factors in the application of the Community Based Tourism concept in the development of the Tourism Area of Pohon Cinta Beach and Lahe Island. Method: used in this research is descriptive qualitative method. Results: This research is 1) the form of application of the concept of Community Bsed Tourism in the development of the Tourism Area of Pohon Cinta Beach and Lahe Island: a) community organization in controlling and developing the tourism process; b) community involvement in building businesses in tourism; c) local community participation in developing tourism; d) empowerment to local communities around the tourist area; and e) benefits to the community in tourism. Conclusion: 1) community organization in controlling and developing the tourism process; 2) community involvement in building businesses in tourism; 3) local community participation in developing tourism; 4) empowerment to local communities around tourist areas; and 5) benefits to the community in tourism. Suggestion: It is expected that with.